Synthesis of a Denitrification Adsorbent with Large Surface Area and Specific Pore Structure for the Removal of Indole from Fuel Oil - Wenming Yang; Yang Cao; Xiaoni Ni; Weihong Hunag; Wanzhen Xu (Adsorption Science & Technology)
We herein report the successful synthesis of molecularly imprinted polymers (MIPs) by surface imprinting methods. The synthesized MIPs were subsequently used to selectively adsorb indole from fuel oil. A new polymerization method (SR&NI ATRP), which combines the atom transfer radical polymerization (ATRP) and reverse atom transfer radical polymerization methods, is applied for the preparation of indole–MIPs. The indole–MIPs prepared have large specific surface area and porosity, as revealed by a series of morphology characterization studies. Static adsorption data indicate that the adsorption capacity of indole–MIPs was 55.8 mg g −1 , and the adsorption equilibrium is achieved in 120 minutes. According to the results of thermodynamic analysis, the adsorption process is spontaneous. In addition, results of kinetics analysis indicated that the adsorption performances of indole–MIPs obey pseudo-second-order model. The Sips and Langmuir equations better fitted with the experimental isothermal data than the Freundlich equation. The selectivity of indole–MIPs was significant and the adsorbent could be reused even after five regeneration cycles.